RELATIONSHIP BETWEEN PRESTIGE VALUE, UTILITARIAN, HEDONIC, AND SELF-ESTEEM MOTIVES TOWARDS ONLINE SHOPPING BEHAVIOR THROUGH SHOPPING INTENTION AND IMPULSE SHOPPING TENDENCY - Alieffira Raizha; Kurniawati Kurniawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Marketplace is currently being disrupted by technology, similar to how the internet and digital platforms explosive rise in the globalization era. The growth of e-commerce changed customer behavior in purchasing items, from offline to online shopping, caused by some motives i.e., hedonic motives, self-esteem, and utilitarian motives. This study aims to comprehend how self-esteem, hedonic value, and utilitarian motivations relate to online shopping behavior, using shopping intention and impulse buying tendency as mediators. This study supports the idea that customers' online purchasing behavior is influenced by their intentions to shop and their propensity for impulsive purchases. 302 respondents who utilize e-commerce were distributed and their responses were gathered. As one of the requirements in this survey, respondents who complete the survey are people who have utilized e-commerce platform for at least three months. AMOS was used to analyze this study. Additionally, this study demonstrates that shopping intention is primary in online shopping behavior. This knowledge will help marketers develop strategies to maximize business performance, such as creating a variety of product categories that can boost customers' self-confidence. The product assortment should also be visually appealing, motivating, and emotionally appealing to the target market. Further discussion and implications are provided in the article.